Antidiabetic and Antioxidant Activities of Peperomia pellucida: A Literature Review - Wardatul Aini; Mona Fathia; Witri Winanda; Khoirul Anwar; Ramadani Fitra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Diabetes mellitus is a chronic metabolic disorder marked by persistent hyperglycemia, oxidative stress, and inflammation, driving interest in natural alternatives to synthetic antidiabetic drugs such as Peperomia pellucida. This literature review synthesizes evidence from PubMed and Google Scholar (last five years) using the terms “Peperomia pellucida”, “ethanol extract”, and “diabetes mellitus”; included studies were original in vitro, in vivo, or review articles reporting phytochemical profiles, enzyme inhibition assays, glycemic outcomes, pancreatic histopathology, inflammatory markers, or antioxidant activity, while studies lacking primary data or methodological detail were excluded. Descriptive and thematic synthesis of selected papers indicates that P. pellucida consistently contains flavonoids, phenolics, alkaloids, tannins, saponins, and terpenoids, and demonstrates antidiabetic effects via α‑amylase and α‑glucosidase inhibition, reduction of blood glucose in animal models, pancreatic tissue protection, and modulation of proinflammatory cytokines, together with robust free‑radical scavenging antioxidant activity. These findings support the plant’s potential as a phytopharmaceutical candidate; however, to enable clinical translation we recommend standardized extract characterization with marker compounds, dose‑response and pharmacokinetic studies, comprehensive acute and chronic toxicity testing, mechanistic investigations in clinically relevant models, and randomized controlled trials with predefined endpoints, alongside development of quality‑control protocols and formulation studies to determine optimal delivery and dosing.